The Prevalence of the Gram Positive and Gram Negative Bacteria in Open Fractures and their Resistance Profiles to Antimicrobial Agents - Aamal Ghazi Mahdi Al-Saadi (Journal of Global Pharma Technology, 2018)
Objectives: We aimed to evaluate the bacteriology of open fractures and to determine the susceptibility patterns of the identified bacterial species to some antimicrobial agents. Methods: 150 superficial swabs were collected from open fracture wounds of patients visited private fractures clinics in Al- Diwaniya city/ Iraq in a period from January to December 2016. Bacterial species recovered from the collected samples were identified by cultural, morphological and biochemical characteristics, then confirmed using Vitek2 compact system. Susceptibility to antimicrobial agents was determined using disc diffusion method. Results: A total of 119 bacterial isolates were obtained from culture positive fracture wounds. The most frequent identified bacterial species was Staphylococcus aureus (23.52%) followed by Acinetobacter spp ( 19.32%) ,then E.coli (14.28%), Pseudomonas spp (11.76%), Enterobacter spp ( 9.24%), Klebsiellaspp (6.72%), Coagulase Negative Staphylococci (5.04%), Citrobacterspp (4.20%), Proteus spp (2.52%), Diphtheroids (0.84),Streptococcus pyogenes (0.84%), Viridans streptococci(0.84%), Micrococcus spp (0.84%).Most of isolates ( 64.70%) were obtained from upper extremities compared with the lower extremities (35.29%). The average resistance rate of Staphylococcus aureus in the current study was (38.31%), the Coagulase Negative Staphylococci( 26.7%), Diphtheroids (70%), Streptococcus pyogenes (40%), Viridans streptococci( 20%), and Micrococcus spp(10%)., Acinetobacter spp (58.36%), E.coli (43.58%), Pseudomonas spp(62.19%), Enterobacter spp (48.21%), Klebsiella spp (40%), Citrobacter spp (32.5%), Proteus spp (35%). Inhibitory effects of citric acid and vinegar on all isolated bacterial species growth were recorded. Conclusion: S. aureus and Acinetobacter spp were the predominant bacterial species isolated from open fractures patients with extensive antibiotic resistance patterns for most of isolated bacterial species underscoring the need to monitor the antibacterial resistance pattern routinely in order to select the right prophylaxis and treatment to open fracture wounds infections. The use of citric acid and vinegar is recommended to effectively eliminate multiple antibiotic resistant bacteria in open fractures.Keywords: Open fractures, Gram positive bacteria, Gram negative bacteria, Antimicrobial agents.